PELATIHAN METODE TAJDIED UNTUK PENINGKATAN MEMBACA AL-QUR’AN SISWA SD MUHAMMADIYAH PROGRAM KHUSUS KOTTABARAT - Andri Nirwana AN; Ahmad Nurrohim; Ilham Jimly Ash-Shiddiqi; Muhammad Azizi; Muhammad Agus; Tifanni Lovely; Ibnu Mas’ud; Sayed Akhyar (UIN Sumatera Utara Medan, 2023)
The Qur'an is a guide for Muslims. But how can a Muslim practice the teachings contained in the Qur'an if he can't even read it. Therefore, the ability to read the Qur'an is very urgent and must be owned by every Muslim. In this case the school takes on its role, namely by teaching to read the Qur'an to students. To facilitate the teaching and learning process to read the Qur'an, SD Muhammadiyah Program Khusus Kottabarat uses the Tajdied method which is used in the practice of reading the Qur'an. The Tajdied method is considered easy and appropriate to use in learning to read the Qur'an, because in this method there are several principles that can be applied in learning the Qur'an which are packaged with songs, and fun sentence structures, making it easier for students to learn. able to read the Qur'an in accordance with the rules of recitation. This study aims to determine the effectiveness of the Tajdied method in learning to read the Qur'an in parallel grade 1 students in the 2021/2022 academic year, at the SD Muhammadiyah Program Khusus Kottabarat. This research method uses a qualitative-descriptive approach. Collecting data through participant observation, interviews, and documentation. From this study, it can be seen that the learning outcomes of reading the Qur'an at the SD Muhammadiyah Program Khusus Kottabarat, because in the parallel 1st grade level increase test there is an increase after using the Tajdied method. Thus, it shows that the application of the tajdied method is able to provide an increase in the ability to read the Qur'an in parallel 1st grade students at the SD Muhammadiyah Program Khusus Kottabarat.